Kako prevajati angleški izraz »sedentary behaviour«? - Kastelic, Kaja (Šport (Ljubljana), 2022)
The English term »sedentary behaviour« is defined as any waking behaviour characterised by low energy expenditure, while in a sitting, reclining, or lying posture. Several different translations of the English “sedentary behaviour” can be found in the Slovenian professional literature, which could hinder the professional development of the field, and present a risk of misinterpretation within professional and general public. Through this paper, we present the English “sedentary behaviour” and how this relatively novel construct paved its way in the scientific literature. Furthermore, we draw attention to the existence of different Slovenian translations of English term “sedentary behaviour” and we discuss about (in) adequacy of each of the translations. According to the bibliometric analysis, the translation “sedentarnost” was the most used in the Slovenian literature to date. However, this translation has not been in established use. Through an argumentative discussion, we propose »sedentarno vedenje« as the most appropriate already used translation for the English term »sedentary behaviour«. We invite interested professional and general public to continue the discussion regarding our proposal, and we highlight that there is a need for a discussion on terminology regarding some other terms in the field of physical activity and health.
Keywords: gibalno vedenje; movement behaviour; sedentarno vedenje; sedentary behaviour; sport; šport; terminologija; terminology